Leadership Competencies as Predictors of Employee Engagement: The Role of Driving Change Through Innovation - Dio, Eric Arthur; Cabrestante, Sheila (Journal of Interdisciplinary Perspectives, 2025)
This study examined whether leadership competencies can predict employee engagement. Using a descriptive-correlational design, the researchers gathered data through total enumeration from 71 middle managers of a publicly listed sugar manufacturing firm in the Philippines, one of the largest in Asia. Descriptive results showed that perceptions of leadership competencies—people development, delivering purposeful results, driving change with innovation, and strategic thinking — were rated high, as was the level of employee engagement, measured in terms of retention, absenteeism, productivity, and growth mindset. To identify which competencies best explain engagement, the researchers conducted a stepwise multiple linear regression analysis. This method tested the relative contribution of each leadership competency to predicting engagement. Findings revealed that only driving change with innovation significantly predicted employee engagement. This highlights the critical role of innovative leadership in fostering engagement. By driving change through creative ideas and approaches, companies can strengthen employee commitment and performance.